How Chinese citizens understand the inflection point of COVID-19 pandemic: insight into formal mathematics and street mathematics - Wang, Yi; Zhang, Lei; Li, Na; Wang, Chongyang; Wang, Lidong (Frontiers in Education, 2025)
IntroductionThe COVID-19 pandemic has fundamentally challenged mathematics education globally, necessitating a deeper understanding of how people utilize mathematical concepts in crisis situations. This study examines how individuals comprehend the pandemic’s inflection point, with a focus on applying mathematical concepts to real-world situations.MethodsThe research employed a mixed-methods approach, collecting data from 1,371 Chinese participants through questionnaire surveys and interviews. The study analyzed participants’ understanding of the pandemic’s inflection point and investigated the sources of their mathematical knowledge.ResultsFindings revealed that despite secondary school mathematics education and media coverage providing relevant knowledge, few participants could accurately explain the concept of an inflection point. Notably, individuals tended to rely on informal mathematical reasoning rather than formal mathematical concepts when interpreting pandemic-related data. Educational background and age significantly affect both response accuracy and the use of mathematics, while field of study only influences the latter.DiscussionThe study identifies a significant disconnect between classroom mathematics and real-world application. This gap suggests the need for educational reforms that emphasize practical applications, knowledge transfer, and out-of-school learning experiences. The findings underscore the importance of developing mathematical literacy that effectively bridges theoretical concepts with practical real-life situations, ultimately contributing to better societal understanding and decision-making during crises.